1962
DOI: 10.1139/b62-028
|View full text |Cite
|
Sign up to set email alerts
|

The Taxonomy, History, and Distribution of Linaria Dalmatica

Abstract: The taxonomy of Linaria dalmatica (L.) Mill. is discussed and a lectotype is selected, viz plant-number XII.10, Linaria latifolia Dalmatica, magno flore Bauh., in the Joachim Burser herbarium, which is preserved in Uppsala. A comprehensive description of the species is given. Two varieties are included: var. dalmatica, native from Yugoslavia to Iran, and var. macedonica (Griseb.) Vandas, indigenous to the mountains of southern Yugoslavia. Photographs of the type specimens of each are presented. L. grandiflora … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Linaria dalmatica is a perennial species that was originally introduced to North America (Canada and the US) as an ornamental plant from its native range in Eurasia (Alex 1962;Vujnovic and Wein 1996;Wilson et al 2005). Synonyms of this species include L. dalmatica ssp.…”
Section: Study Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linaria dalmatica is a perennial species that was originally introduced to North America (Canada and the US) as an ornamental plant from its native range in Eurasia (Alex 1962;Vujnovic and Wein 1996;Wilson et al 2005). Synonyms of this species include L. dalmatica ssp.…”
Section: Study Organismsmentioning
confidence: 99%
“…macedonica (Griseb) (Alex 1962;Vujnovic and Wein 1996;Weber and Wittmann 2001;USDA, NRCS 2009a). Due in part to substantial morphological and genetic variation, the taxonomy of L. dalmatica in the introduced and native ranges remains unclear (Alex 1962;Wilson et al 2005; Gaskin personal communication). Adding to this confusion, L. dalmatica can hybridize with L. vulgaris (Ward et al 2009).…”
Section: Study Organismsmentioning
confidence: 99%
“…dalmatica (L.) Maire & Petitm.] (Plantaginaceae) or Dalmatian toadflax was introduced into North America from Europe near the turn of the 20th century (Alex ) and is a noxious weed of natural areas and dry rangelands in 12 western US states and in two Canadian provinces (USDA‐NRCS ). Linaria dalmatica is native to the Dalmatian coast of the former Yugoslavia to Romania, Bulgaria, Albania, Greece, Crete, Turkey, Azerbaijan, Syria, Iran and Iraq (Alex ) and has been a target of biological control in North America since the 1960s (Wilson et al .…”
Section: Introductionmentioning
confidence: 99%
“…Observations of toadflax suggest that it tends to invade disturbed areas, open rocky sites, well-drained, coarse-textured soils, and sloped areas, particularly those with a southern aspect (Alex 1962;Robocker 1974;Vujnovic and Wein 1996;Lajeunesse 1999;Rew et al 2005). Experimental studies in mixed-grass prairie have found toadflax to be favored by both low species richness and high nitrogen availability (Maron and Marler 2008;Blumenthal 2009).…”
Section: Introductionmentioning
confidence: 99%